Akuntabilitas Pengelolaan Keuangan pada Yayasan Pendidikan Berbasis Keagamaan: Studi Kasus Yayasan Ummul Qurro’ Batam - Farichah, Norlaili; Tipa, Handra (Economic Reviews Journal, 2026)
Financial management accountability is an important aspect for religious-based educational institutions, given that the funds managed come from the community, students, and the government. This study aims to analyse the implementation of financial recording systems, the effectiveness of internal control systems, and the competence of human resources (HR) in supporting the realisation of financial management accountability at the Ummul Qurro' Batam Foundation. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants include foundation administrators, treasurers, administrative staff, and heads of educational units directly involved in financial management. The results of the study show that the financial recording system at the Ummul Qurro' Batam Foundation has been running routinely, but it is still simple and does not fully refer to non-profit accounting standards. The internal control system is implemented through a mechanism of approval and supervision by the leadership, but it is not yet supported by standard written procedures. Human resource competence in the field of finance is still limited, which affects the quality of financial reporting. This study concludes that the integration of financial recording, internal control, and human resource competence greatly determines the level of accountability in the foundation's financial management.